Geomorphological analysis of the cuesta-peripheral depression: Case study of the Passa Cinco river watershed - de Souza, Tissiana de Almeida [UNESP]; de Andrade, Rafael Vilela [UNESP]; Lupinacci, Cenira Maria [UNESP] (Revista Brasileira de Geografia Fisica, 2020)
A B S T R A C T The relief of São Paulo is characterized by the presence of long cuesta, whose origin causes discussion until the present day. Thus, the objective of this research is to analyze the morphostructural characteristics of the Passa Cinco River watershed, situated at transition zone of Cuestas-Peripheral Depression, constituting significative example of this relief system, taking in consideration the complexity of existing forms, that include extense continuous cuesta scarp and buttes of different sizes, extensions and characteristics. The data to analyze the study area were obtained through the integrated interpretation of the Geomorphological, Declivity, Drainage Density, Depth of Drainage and Lineation maps, in 1:50.000 scale. Beyond circumdenudation, considered the classic process of origin of these two relief macrocompartments, tectonic factors also need to be evaluated in order to have a better understanding of these relief forms. These factors are responsible for the acceleration of erosive processes promoted by river courses in some sectors, collaborating with the circumdenudation process, as with the local variation of the Cuesta Front and buttes. Thus, it is understood that the technical procedures allowed to obtain data that demonstrate the complexity involved in the elaboration of the relief in this transition sector, being able to be extended to others areas of the interior of the state of São Paulo with this same relief characteristics.
Análise geomorfológica da transição cuestas-depressão periférica: A alta bacia do rio Passa Cinco(SP) como estudo de caso
Keywords: Declivity; Depth of drainage; Drainage density; Lineation